Recommended immunization schedules for adults: clinical practice guidelines by the Escmid Vaccine Study Group (EVASG), European Geriatric Medicine Society (EUGMS) and the World Association for Infectious Diseases and Immunological Disorders (WAidid) - Esposito, Susanna; Bonanni, Paolo; Maggi, Stefania; Tan, Litjan; Ansaldi, Filippo; Lopalco, Pier Luigi; Dagan, Ron; Michel, Jean-Pierre; Damme, Pierre van; Gaillat, Jacques; Prymula, Roman; Vesikari, Timo; et al. (Human vaccines & immunotherapeutics, 2016)
Rapid population aging has become a major challenge in the industrialized world and progressive aging is a key reason for making improvement in vaccination a cornerstone of public health strategy. An increase in age-related disorders and conditions is likely to be seen in the near future, and these are risk factors for the occurrence of a number of vaccine-preventable diseases. An improvement in infectious diseases prevention specifically aimed at adults and the elderly can therefore also decrease the burden of these chronic conditions by reducing morbidity, disability, hospital admissions, health costs, mortality rates and, perhaps most importantly, by improving the quality of life. Among adults, it is necessary to identify groups at increased risk of vaccine-preventable diseases and highlight the epidemiological impact and benefits of vaccinations using an evidence-based approach. This document provides clinical practice guidance on immunization for adults in order to provide recommendations for decision makers and healthcare workers in Europe. Although immunization is considered one of the most impactful and cost-effective public health measures that can be undertaken, vaccination coverage rates among adults are largely lower than the stated goal of ≥ 95% among adults, and stronger efforts are needed to increase coverage in this population. Active surveillance of adult vaccine-preventable diseases, determining the effectiveness of the vaccines approved for marketing in the last 5 y, the efficacy and safety of vaccines in immunocompromised patients, as well as in pregnant women, represent the priorities for future research.
Gesehen am 11.05.2020